Hasan Turabi's Concept of Fiqh Democracy and Its Relevance in Modern Political Contexts - Oseolla Savana; Lutfiyah; Erlina Laily Nur Afifa; Ariibah Radita Ayu Candrika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Hasan Turabi's thoughts on the fiqh of democracy offer an integrative approach between Islamic principles and modern democratic systems of government. He emphasizes that democracy in Islam must be based on shura (deliberation), which allows for the active participation of the people in political decision-making. In the concept of fiqh of democracy developed, Turabi emphasizes several key aspects, namely the application of sharia through consensus (ijma'), respect for the freedoms and rights of the people, social justice, and separation of powers to prevent authoritarianism. These principles were designed to keep the Islamic political system relevant to the demands of modernity without abandoning the fundamental teachings of the religion. His thought is significant for Muslim countries that are still seeking a balance between Islamic values and contemporary democratic systems. Through a literature review of his works and several related sources, this article explores how fiqh of democracy can be an alternative solution in building a more inclusive, just, and participation-oriented system of government. Thus, Turabi's thoughts can be relevant to be the main reference in efforts to integrate Islam and democracy in modern politics, providing a new perspective in equitable governance.